Nanoparticulates reduce tumor cell migration through affinity interactions with extracellular migrasomes and retraction fibers. Issue 7 (15th June 2022) - Cheng, Yuxi; Ren, Junji; Fan, Shumin; Wu, Peiyao; Cong, Wenshu; Lin, Yuxing; Lan, Shaojie; Song, Siyang; Shao, Bin; Dai, Wenbing; Wang, Xueqing; Zhang, Hua; et al.
Abstract : NPs bind to retraction fibers and migrasomes during tumor cell migration. Such Nano–ECM interactions could alter cell morphology, limit cell motion range, change cell adhesion and inhibit tumor cell metastasis in vitro and in vivo . Abstract : Nano–tumor interactions are fundamental for cancer nanotherapy, and the cross-talk of nanomedicines with the extracellular matrix (ECM) is increasingly considered essential. Here, we specifically investigate the nano–ECM interactivity using drug-free nanoparticulates (NPs) and highly metastatic cancer cells as models. We discover with surprise that NPs closely bind to specific types of ECM components, namely, retraction fibers (RFs) and migrasomes, which are located at the rear of tumor cells during their migration. This interaction is observed to alter cell morphology, limit cell motion range and change cell adhesion. Importantly, NPs are demonstrated to inhibit tumor cell removal in vitro, and their anti-metastasis potential is preliminarily confirmed in vivo . Mechanically, the NPs are found to coat and form a rigid shell on the surface of migrasomes and retraction fibers via interaction with lipid raft/caveolae substructures. In this way, NPs block the recognition, endocytosis and elimination of migrasomes by their surrounding tumor cells. Thereby, NPs interfere with the cell–ECM interaction and reduce the promotion effect of migrasomes on cell movement. Additionally, NPs trigger alteration of the expression of proteins related to cell-cell adhesion and cytoskeleton organization, which also restricts cell migration. In summary, all the findings here provide a potential target for anti-tumor metastasis nanomedicines.